Alcohol, Aggression, and Violence: From Public Health to Neuroscience - Sontate, Kajol V.; Rahim Kamaluddin, Mohammad; Naina Mohamed, Isa; Mohamed, Rashidi Mohamed Pakri; Shaikh, Mohd. Farooq; Kamal, Haziq; Kumar, Jaya (Frontiers in Psychology, 2021)
Alcohol has been associated with violent crimes and domestic violence across many nations. Various etiological factors were linked to chronic alcohol use and violence, including psychiatric comorbidities of perpetrators such as personality disorders, mood disorders, and intermittent explosive disorders. Aggression is the precursor of violence, and individuals prone to aggressive behaviors are more likely to commit impulsive violent crimes, especially under the influence of alcohol. Findings from brain research indicate long-term alcohol consumption induced morphological changes in brain regions involved in self-control, decision making, and emotional processing. In line with this, the neurochemical anomalies were seen in aggressive individuals such as serotonergic and dopaminergic also increase their susceptibility to commit violent crimes in the presence of alcohol in their system. In relation to this, the review article intends to investigate the influence of alcohol on aggression with a socio-psychological and neuroscientific perspective by looking into comorbidity of personality or mood disorders, state of the mind during consumption, types of beverages, environmental trigger, neurological neurochemical changes, and gender differences that influence individual responses to alcohol intake and susceptibility to intoxicated aggression.